Radiofrequency ablation-combined multimodel therapies for hepatocellular carcinoma: Current status. Issue 1 (1st January 2016) - Chen, Lumin; Sun, Jihong; Yang, Xiaoming
Highlights: Hepatocellular carcinoma is the leading cause of cancer-related death. RFA is widely applied in the management of HCC. Combination uses of RFA with other therapies offer more effective treatment of HCCs. It is necessary to opitimize and establish the best RFA-integrated multimodal therapy strategy for management of HCCs. Abstract: Radiofrequency ablation (RFA) is widely accepted as a first-line interventional oncology approach for hepatocellular carcinoma (HCC) and has the advantages of high treatment efficacy and low complication risk. Local control rates equivalent to hepatic resection can be reached by RFA alone when treating small HCCs (<2 cm) in favorable locations. However, local tumor progression and recurrence rates with RFA monotherapy increase sharply when treating larger lesions (>3 cm). To address this clinical problem, recent efforts have focused on multimodel management of HCC by combining RFA with different techniques, including percutaneous ethanol injection, transarterial chemo-embolization, targeted molecular therapy, nanoparticle-mediated therapy, and immunotherapy. The combination strategy indeed leads to better outcomes in comparison to RFA alone. In this article, we review the current status of RFA-combined multimodal therapies in the management of HCC.